(untitled) (Biological Sciences - PJSIR, 2006)
A study on the ash of Lakhra lignite coal and the bottom/fly ash, obtained from combustion of Lakhra lignites in atmospheric fluidized bed combustor (AFBC) was carried out. It has been observed that the absence of alkali metals was of significant importance, as alkali metals were responsible for agglomeration in the AFBC.